Nós primatas em linguagem: relações lingüísticas como um processo biológico - Humberto Luiz Galupo Vianna (2006)
The aim of the present thesis is to approach linguistic phenomena as biological processes, through the proposition of a descriptive model based on four conceptual operations: 1) to consider the organism as a system of relations, i.e., ontogenic, ecological and linguistic relations; 2) to treat cognition as a system involving an organism in its medium, and, not, as a trait located in, or produced by, the organism physiology; 3) to abandon the dichotomy between communication and language in the phenomenology of the living, adopting, instead, a framework focused on ecological and linguistic relations; 4) and to consider language as the co-ontogenic relations established between two or more organisms participating in the same interactional net, and a process of conservation of a way of living. The present work reaffirms the centrality of evolutionary discussion to approach language as a biological process, embedding both the evolutionary approach and the descriptive model used here in the following partial and complementary theoretical frameworks: the dialectical biology of Richard Lewontin and others, the Developmental Systems Theory (DST), the Biology of Cognition (BC) and the hierarchical selection and evolutionary pluralism of Stephen Jay Gould. Following a discussion on non-human language, cognition and culture, based on the literature in language evolution, primatology and comparative and developmental psychology, the descriptive model proposed is applied to actual interactions observed among nonhuman great apes. Besides its strong interdisciplinary character, the present work aims at offering, through the descriptive model and discussions proposed, a contribution to the linguistic studies, in special their investigation on the inter-relations between language, cognition and culture.